ANALISIS PENGARUH RASIO KEUANGAN PADA HARGA SAHAM ASURANSI - Fitri, Nor Alsuraya Desi; Hafizah, Nurul; Purwanto, Aji (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This journal will discuss the analysis of the influence of financial ratios on insurance stock prices. Insurance is one of the financial companies listed on the Indonesia Stock Exchange. The development of insurance companies is rational and inevitable, because most entrepreneurs and people have a tendency to avoid the risk of loss or divert the risk of financial loss. This attracted researchers to analyze studies on the factors that affect the stock prices of insurance companies. The purpose of this study is to analyze the effect of the insurance company's claim expense ratio on the stock price. The types of research applied to this study are Descriptive Method and Qualitative Method. The type of data used is Secondary Data. Secondary data is data that contains information and theories used to support research. The data collection technique used in this study is a documentation study, which is the collection of supporting data in the form of published financial reports literature to get an overview of the problem to be studied